DO LARGE FIRMS BENEFIT MORE FROM R&D INVESTMENT? - Ibhagui, Oyakhilome (The European Journal of Applied Economics, 2019)
We examine the importance of firm size in the relationship between research & development (R&D) and firm performance. Our empirical analysis, based on data drawn from Nasdaq-listed companies for the period 2002 to 2017, shows that R&D can have effects of varying magnitudes on firm performance, depending on firm size. When R&Dweakens firm performance, the negative effects are more pronounced for small-sized firms, but when the impact of R&D is positive, leading to an improvement in firm performance from increased R&D, largesized firms tend to reap most of the benefits. Accordingly, we show that firm size matters in understanding the scale of the impact of R&D on firm performance.